EGY ÁLLAMJOGI FIKCIÓ SORSA. AZ NDK ELPORLADÁSA ÉS A KELETNÉMET MENEKÜLTVÁLSÁG 1989-BEN - Tóth, Imre (Közép-Európai Közlemények, 2020)
The 1980s crises on the periphery and half periphery of the system led to a rapid collapse of the system of state socialism. The process of change led to a new independence of the former satellite nations. Poland and Hungary were the leading agents of change among the nations of East and Central Europe. These changes fed on each other and suddenly accelerated so that events which earlier would have been unbelievable appeared in an unusual way, especially in the summer of 1989 on the Austrian Hungarian border. The Communist leadership in East-Berlin stood by helplessly, as ever more East Germans fled from their hopeless situation. Their first goal was to settle in West Germany. The easiest way to leave the socialist system behind seemed to be through Hungary. Their hopes had been fed since 2nd May, 1989 by the discussions which had begun between Austria and Hungary on dismantling the Iron Curtain. Strictly classified bilateral negotiations between Hungary and West-Germany led to the opening of the border on September 11 and East German refugees were evacuated from Hungary. The border breakthrough, the “exodus” of East German refugees and the weakening of the East German dictatorship led to the German „reunification”, which also meant the reunification of Europe.